STUDI TENTANG NILAI - NILAI PANCASILA YANG TERKANDUNG DALAM UPACARA ADAT PERKAWINAN MASYARAKAT PETALANGAN DI KEC. BANDAR – PETALANGAN – PELALAWAN: (Study of Pancasila Values in Traditional Marriage Ceremony at Petalangan Kec. Bandar Petalangan Palalawan) - Jumili Arianto; Afrizal Yurnalis (UIR Press, 2015)
This research was supported by pancasila as a view of life of indonesia nation, because pancasila essentially is not only a result of thinking contemplation of a person or group of people as ideologies in the world. However it is extracted from values of manners, culture, and religious contained in indonesia nation. As well as the implementation of traditional marriage ceremony of Petalangan society in district of Bandar Petalangan Pelalawan done from generations to generations. This formulation of problem was whether the values of pancasila contained in traditional marriage ceremony of Petalangan society in district of Bandar Petalangan Pelalawan. The purpose of this research is to determine the values of pancasila contained in traditional marriage ceremony of Petalangan society in district of Bandar Petalangan Pelalawan. The population in this research was all societies of district of Bandar Petalangan Pelalawan which had married. While the technique of sampling using Purposif Sampling technique as many as 50 people from 4.038 households who were married. The technique of accumulating data used in this research was using queastionnare, interviewing and documenting. The technique of data analysis used in this research was descriptive quantitative. The result of this research indicated 6 dominant indicators that were values of pancasila with average of the respondents answer percentage to the answer “yes” for (91,47%), and 6 less dominant indicators that were values of pancasila with average of the respondents answer percentage to the answer “yes” for (79,33%). So it could be totalled from the result of percentage of 50 respondents saying that there were values of pancasila in traditional marriage ceremony of Petalangan society for (85,4%), included in the benchmark “yes” were among 50,01%-100%. So in this research proved that traditional marriage ceremony of Petalangan society in district of Bandar Petalangan Pelalawan contained values of pancasila.